ANALISIS PENGGUNAAN INSTAGRAM AKUN @WEAR.MOUNA SEBAGAI MEDIA KOMUNIKASI PELANGGAN DALAM PENJUALAN ONLINE BUSANA MUSLIMAH (Studi Kasus pada Alumni Ma’had Al-Zaytun) - Dzulfahira Yusuf; Wiena Safitri; Muhammad N. Abdurrazaq (STKIP Subang, 2024)
This research was conducted on the @Wear.mouna Instagram account, the target of which was the communication process that occurred on the @Wear.mouna Instagram account to customers in selling Muslim clothing. This research looks at the customer communication process carried out by @Wear.mouna in sales via Instagram social media which is managed by